Restriction endonuclease cleavage map of mitochondrial DNA from Aspergillus nidulans. - Stepień, P P (1978)
Mitochondrial DNA of the ascomycete fungus Aspergillus nidulans, a circular molecule of 31 500 base pairs, is cleaved by restriction endonucleases Eco R I, Hind II, Hind III and Bgl II into 3, 7, 9 and 5 fragments, respectively. The relative positions of the cleavage sites could be mapped by analysis of fragments obtained by double enzyme digestions of whole DNA and by complete and partial redigestion of isolated restriction fragments.